Investment in Swedish Manufacturing: Analysis and Forecasts - Bengt Assarsson; Claes Berg; Per Jansson (Sveriges Riksbank, 1999)
This paper uses a neoclassical investment model extended with installation costs for capital, agency costs for investment financing, and the possibility of the firm being output constrained as a framework for an empirical analysis of investment behaviour in the Swedish manufacturing industry. The theory is implemented within a multivariate error-correction approach on data covering the time period 1951 to 1995, and we gain the following main results: (1) Tobins average Q is not the sole determinant of investment, neither in the short nor in the long run, and other variables like real output and capital gearing also affect investment activity; (2) the out-of-sample forecasts of the model track the evolution of actual investment growth quite impressively, especially at short- and medium-term horizons (1-2 years); (3) a relative equity-price variable is shown to constitute a good approximation of average Q, both for empirical modelling in general and forecasting in particular.
Keywords: C32; E22; E27; 330; Forecasting investment; Multivariate error-correction model; Neoclassical investment theory; Tobin's Q